Julid Fi Sabilillah: The Netizen Jihad Movement in the Israel-Palestine Conflict Through the Maqashid Syariah System Approach - Kurniawan, Achmad Alfan (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
The Israel-Palestine conflict, marked by widespread human rights violations, has prompted global responses, including digital activism through the julid fi sabilillah movement. Despite the negative connotations of julid, it is framed as contemporary jihad to counter narratives of Israeli apartheid, regardless of any contradictions with Islamic principles of justice and ethics. This study aims to assess the validity of the movement through the maqashid syariah framework. Utilizing a descriptive-analytical technique in empirical legal research, data from books, journals, and social media content were analyzed through data reduction, presentation, triangulation, and the features of the maqashid syariah system approach. Research indicates that julid fi sabilillah may be classified as a fardu kifayah if it adheres to normative standards, such as a sincere intention, evidence-based analysis, and the prevention of defamation (ghibah) and misinformation (fitnah). The movement actualizes the interrelated hierarchy of maqashid syariah by advocating for global justice and human rights (universal objective), digital literacy (specific), and moral pressure (partial). The results highlight the need to integrate internet activism with sustained collective action and the idea of amar ma’ruf nahi munkar to prevent slacktivism. This study offers an evaluative framework for Muslim communities to contextualize and ethically address digital jihad.